(untitled) (Ameghiniana, 2013)
The evolutionary grade of some bones of a Megatherium americanum Cuvier, 1796, found in the "Meflano Invasor" formation, allows the determination of its age. A new name for the formation is suggested: Forniation La Movediza. The age is considered as neopleistocene, probably its upper part, on the ground of the •high specialization of the . specimen studied.